PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN DI KELAS V SD - Susanti, Susi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Through this research, the writer applies Eksperimen Method in processes learning for there are many student. Observational stage is describe to plot, implement, and step-up study results. Type of this research is observational action braze, with use qualitative approaching and quantitative one consisting of two cycles. Observational student of class five and observational. Analisis‘s result to learning planning on. Cycle is 69,64% experience step-ups on the second cycle, by derived 92,85%. Result observinging to activity learns in learning on I, cycle is 73,72% experience step-ups on the second cycle 93,11%. Result observinging to student activity in learning on I cycle is 69,61% experience step-ups on the second cycle, by derived 90,27%. Learned result before perform research average 62,39 on the second cycle, average 73,5. In short, the research action class uses eksperimen could increase the student’s result for exact science course. Kata Kunci : hasil belajar, IPA, metode, pembelajaran, dan metode eksperimen